Enzymatic Esterification of Betulinic Acid - S, Omar; F.H, Ahmad; H, Hassan; N.H, Faujan; M, Basri (Malaysian Journal of Science, 2005)
Esterification of betulinic acid with 1-decanol in chloroform was described. It gave the desired betulinic acid ester. The esterification as expected occurred at C-28 position. The conversion gave high yield of the desired ester after 24 hours of reaction. The reaction was carried out at 37Ã‚Â°C in horizontal water bath shaker. Lipozyme, an immobilized lipase, was used as the catalyst. The product was analysed using spectrocopic data. To the best of our knowledge this is the first report in which betulinic acid ester was prepared using enzymatic reaction.